High-performance polypropylene chemical pipe and preparation method thereof

By introducing modified carbon nanotubes and hydrotalcite into polypropylene pipes, their antistatic and flame-retardant properties are improved, solving the problem of flammability and explosion of polypropylene pipes and ensuring the safety of chemical production.

CN121699290APending Publication Date: 2026-03-20JUZHENGYUAN (SHENZHEN) NEW MATERIAL TECHNOLOGY R&D CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610040271.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-13
Publication Date
2026-03-20

AI Technical Summary

Technical Problem

Existing polypropylene pipes are flammable and explosive, and have poor antistatic properties, posing fire and static electricity hazards and failing to meet the safety requirements of chemical production.

Method used

By preparing antistatic and flame-retardant materials, the conductivity and flame-retardant properties of the materials are improved by modifying the surface of multi-walled carbon nanotubes with silver nanoparticles and the layered structure of hydrotalcite, combined with compound antioxidants.

Benefits of technology

It significantly improves the antistatic and flame-retardant properties of polypropylene pipes, reduces the risk of fire, and ensures the safety of chemical production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121699290A_ABST
    Figure CN121699290A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, in particular to a high-performance polypropylene chemical pipe and a preparation method thereof. The preparation method comprises the following steps: firstly, preparing a compound antioxidant; and uniformly mixing the processing aid PPA, calcium stearate, beta nucleating agent powder and toner, and mixing with the compound antioxidant to obtain the additive. And mixing the polypropylene resin, the antistatic material, the composite flame-retardant material and the additive, and carrying out melt extrusion, cooling and traction to obtain the finished product of the high-performance polypropylene chemical pipe. The finished product prepared by the invention has excellent flame retardance and antistatic property, so that the product has wide application prospects in the technical field of high polymer materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, specifically to a high-performance polypropylene chemical pipe and its preparation method. Background Technology

[0002] Polypropylene, abbreviated as PP, is a conventional thermoplastic. Polypropylene boasts advantages such as low density, high heat resistance, excellent chemical stability, mechanical properties, and electrical insulation. In the pipe industry, plastic pipes account for approximately 50%, with PP consistently ranking third. In the core field of internal hot and cold water pipes, PP, with its excellent heat resistance, reliable connections, and long lifespan, holds a market share exceeding 80%, becoming a pillar material for hot and cold water systems. PP pipes feature a unique heat-fusion connection method, along with their excellent heat resistance and cost-effectiveness, making them the preferred choice for hot and cold water pipes for the foreseeable future. In the chemical industry, β-PPH pipes are the preferred choice due to their outstanding chemical corrosion resistance. Because the β-crystalline structure effectively disperses impact energy, improving the product's impact resistance, it also possesses high-temperature resistance and creep resistance. β-PPH primarily achieves its superior performance through a β-crystalline structure induced by a β-nucleating agent during polymerization, thus altering the crystal type to form a high-performance polypropylene pipe material.

[0003] However, chemical production environments are complex and often involve flammable and explosive chemicals. Ordinary polypropylene pipes are flammable and, once exposed to a source of ignition or high temperature, can easily cause fires or even explosions, seriously threatening the safety of people and property. Therefore, improving the flame-retardant properties of the pipes can slow down the burning rate and reduce the spread of fire in the event of a fire, buying valuable time for rescue and evacuation. Simultaneously, static electricity is easily generated during chemical production processes due to material flow and friction. If the pipes have poor antistatic properties, the accumulated static electricity can lead to electrostatic discharge, becoming an ignition source for flammable and explosive substances. Pipes with good antistatic properties can effectively dissipate static electricity, avoiding the dangers caused by static electricity.

[0004] To overcome the shortcomings of existing technologies, this invention provides a high-performance polypropylene chemical pipe and its preparation method. Summary of the Invention

[0005] The purpose of this invention is to provide a high-performance polypropylene chemical pipe and its preparation method, so as to solve the problems raised in the prior art.

[0006] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing high-performance polypropylene chemical pipes includes the following steps: mixing one or more of the following in proportion to obtain a compound antioxidant; After the processing aid PPA, calcium stearate, β-nucleating agent powder and color powder are mixed evenly, they are then mixed evenly with the compound antioxidant to obtain the additive. The polypropylene resin, additives, and auxiliaries are then mixed, melt-extruded, cooled, and drawn to obtain the finished product.

[0007] In a more optimized manner, the content of each component in the finished product is as follows (by mass fraction): tris(2,4-di-tert-butyl)phosphite 0.1%-0.5%, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate octadecyl alcohol 0.1%-0.5%, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] 0.1%-0.5%, tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanuric acid 0.1%-0.5%, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)triazine-2,4,6 -(1H,3H,5H)trione 0.1%-0.5%, 2,4,6-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)trimethylbenzene 0.1%-0.5%, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane 0.1%-0.5%, processing aid PPA 0.01%-0.1%, calcium stearate 0.1%-0.5%, β-nucleating agent powder 0.1%-0.5%, colorant 0.1%-0.5%, 0-23% additives, balance polypropylene resin; melt extrusion temperature is 180-210℃.

[0008] In a more optimized manner, the additive is a mixture of antistatic material and composite flame retardant material in a mass ratio of (1.5-3.0):(15-20).

[0009] A more optimized preparation process for antistatic materials is as follows: Step S1: Add multi-walled carbon nanotubes to the acid solution and stir at 85-95℃ for 30-40 min. After the reaction, cool, dilute, filter, wash with water, dry, and grind to obtain modified carbon nanotubes. Add the modified carbon nanotubes to the mixed solution and stir at 25-30℃ for 2-3 h. After the reaction, wash, dry, and grind to obtain pretreated carbon nanotubes. Step S2: Add the pretreated carbon nanotubes to a 3-5 wt% silver ammonia solution and stir at 25-30℃ for 20-30 min. Then add a 5-6 wt% glucose solution and continue stirring for 3.5-4.0 h. After stirring, filter, wash with water, dry and grind to obtain CNTs-Ag. Step S3: Add CNTs-Ag to ethanol, disperse evenly by ultrasonication, then add 2-propen-1-thiol, and stir the reaction at 25-30℃ for 7-8 hours under a nitrogen atmosphere. After the reaction is completed, wash with alcohol, filter and dry to obtain propylene-based antistatic material. Step S4: Under a nitrogen atmosphere, add isopentenyl alcohol polyoxyethylene ether, maleic anhydride, and propylene antistatic material to deionized water, stir evenly, add hydrogen peroxide, and then add ferrous chloride aqueous solution dropwise. After the addition is complete, react at 35-40℃ for 5-7 hours. After the reaction is complete, cool, wash, distill under reduced pressure, precipitate, filter, wash, and dry to obtain the antistatic material.

[0010] In a more optimized manner, the acid solution includes 8.3-8.5 mol / L concentrated nitric acid and 16-18 mol / L concentrated sulfuric acid in a volume ratio of 1:1; the mixed solution includes 0.12-0.14 g / L stannous chloride and 1.0-1.1 mol / L hydrochloric acid; and the mass-volume ratio of the pretreated carbon nanotubes, silver ammonia solution, and glucose solution is 2 g: 50 mL: (40-50) mL.

[0011] In a more optimized manner, the mass-to-volume ratio of CNTs-Ag to 2-propen-1-thiol is 2 g: (0.4-0.5) mL; the reaction mass ratio of isopentenyl alcohol polyoxyethylene ether, maleic anhydride, and propylene-based antistatic material is 3:1: (0.5-0.7).

[0012] A more optimized preparation process for composite flame-retardant materials is as follows: Step S1: Under a nitrogen atmosphere, add hydrotalcite to the mixed solution and stir at 50-55℃ for 30-40 min. After stirring, slowly add silane coupling agent solution, adjust the pH of the solution to 3-4, and reflux at 80-90℃ for 25-30 h. After the reaction is completed, cool, filter, wash and dry to obtain modified hydrotalcite material. Step S2: Add hexachlorocyclotriphosphazene and the acid-binding agent ethylenediaminetetraacetic acid to tetrahydrofuran, and disperse evenly by ultrasonication to obtain a reaction solution; add the modified hydrotalcite material to tetrahydrofuran, disperse evenly by ultrasonication, and then add the reaction solution. Stir and react at 60-65℃ for 9-12 hours. After the reaction is completed, cool, filter, wash and dry to obtain the flame-retardant hydrotalcite material. Step S3: Add tannic acid to acetonitrile, stir evenly at 55-60℃, then add flame-retardant hydrotalcite material, continue stirring and heating for 30-40 minutes, then raise the temperature to 75-80℃, and add anhydrous magnesium chloride at the same time, continue stirring and reacting for 2.5-3.0 hours, then add acid-binding agent pyridine, and continue reacting for 1-3 hours. After the reaction is completed, filter, wash and dry to obtain flame-retardant material; Step S4: Add the flame retardant material to deionized water, disperse it evenly, and then add 16-17 g / L of ferric nitrate solution dropwise. After the addition is complete, react at 25-30℃ for 3.0-3.5 h. After the reaction is complete, filter, wash, dry, and grind to obtain the composite flame retardant material.

[0013] In a more optimized manner, in step S1, the mixed solution includes ethanol and deionized water in a volume ratio of (1.0-1.2):3; the silane coupling agent solution includes γ-aminopropyltriethoxysilane, ethanol, and deionized water in a mass-volume ratio of (0.10-0.12) g:10 mL:1 mL; and when preparing the modified hydrotalcite material, the reaction mass ratio of hydrotalcite and γ-aminopropyltriethoxysilane is 1:(0.08-0.10).

[0014] In a more optimized manner, the reaction mass ratio of hexachlorocyclotriphosphazene, ethylenediaminetetraacetic acid, and modified hydrotalcite material is 1:0.63:(18-20); the reaction mass ratio of tannic acid and flame-retardant hydrotalcite material is 1:(15-17).

[0015] The beneficial effects of this invention are: The key feature of this invention is that multi-walled carbon nanotubes are sequentially subjected to acid treatment and activation pretreatment to obtain pretreated carbon nanotubes. The pretreated carbon nanotubes, silver ammonia solution, and glucose solution are then mixed. As the reaction proceeds, silver ions adsorbed on the surface of the carbon nanotubes are reduced to silver atoms. These silver atoms gradually aggregate to form silver nanoparticles, which are then deposited on the surface of the carbon nanotubes, ultimately forming CNTs-Ag. CNTs-Ag is then mixed with 2-propen-1-thiol, and through a coordination reaction between the thiol group and silver, propylene groups are introduced into the surface of CNTs-Ag to obtain an propylene-based antistatic material. Finally, isopentenyl polyoxyethylene ether, maleic anhydride, and the propylene-based antistatic material are mixed and polymerized under the action of an initiator to obtain the antistatic material.

[0016] Multi-walled carbon nanotubes (MWCNTs) possess excellent electrical conductivity, and their unique one-dimensional tubular structure and large aspect ratio enable rapid electron transport within the tubes. After acid treatment and activation pretreatment, the active groups provide attachment sites for the subsequent loading of silver nanoparticles, facilitating the construction of a continuous conductive network and laying the foundation for antistatic properties. In subsequent reactions, silver atoms gradually aggregate to form silver nanoparticles and deposit on the surface of carbon nanotubes, further enhancing the material's conductivity. Electrons can rapidly transfer between the silver nanoparticles and carbon nanotubes, significantly improving the material's electron transport capability and thus significantly enhancing its antistatic performance. Furthermore, the introduction of propylene groups provides a basis for the copolymerization reaction of isopentenyl polyoxyethylene ether, maleic anhydride, and propylene-based antistatic materials. The ether oxygen atoms in the polyether segments of isopentenyl polyoxyethylene ether have charge-transfer capabilities, effectively transferring charge. Therefore, the prepared antistatic material achieves a synergistic effect of multiple factors—multi-walled carbon nanotubes providing the basic conductive channels, silver nanoparticles enhancing conductivity, and polymerization products providing stability and synergistic effects—resulting in excellent antistatic properties.

[0017] The key feature of this invention is that a hydrotalcite and silane coupling agent solution are mixed and refluxed to introduce amino groups onto the surface of the hydrotalcite structure, resulting in a modified hydrotalcite material. Then, hexachlorocyclotriphosphazene, ethylenediaminetetraacetic acid (EDTA), and the modified hydrotalcite material are mixed to undergo a nucleophilic substitution reaction, yielding a flame-retardant hydrotalcite material. This step, by setting the mass ratio of hexachlorocyclotriphosphazene, EDTA, and the modified hydrotalcite material to 1:0.63:(18-20), ensures that 55-60% of the chlorine groups in the hexachlorocyclotriphosphazene react in this step, allowing the remaining chlorine groups to participate in the next reaction. Specifically, the hydroxyl groups of tannic acid and the remaining chlorine groups in the flame-retardant hydrotalcite material continue to undergo nucleophilic substitution, resulting in a flame-retardant material. Finally, a ferric nitrate solution is added dropwise to the flame-retardant material, where tannic acid chelates iron ions, resulting in a composite flame-retardant material, where the iron ions catalyze carbonization.

[0018] Hydrotalcite, a layered bimetallic hydroxide, possesses a unique layered structure and composition. When heated, it decomposes and absorbs a large amount of heat, releasing carbon dioxide and water vapor, thus diluting the concentration of oxygen and combustible gases and inherently exhibiting flame-retardant properties. Furthermore, the introduction of amino groups into hydrotalcite provides reaction sites for subsequent reactions with hexachlorocyclotriphosphazene, thereby further constructing a flame-retardant system. Hexachlorocyclotriphosphazene and the modified hydrotalcite material undergo a nucleophilic substitution reaction, introducing flame-retardant phosphorus and nitrogen groups onto the surface of the modified hydrotalcite material, forming a flame-retardant hydrotalcite material. Further addition of tannic acid reacts with the flame-retardant hydrotalcite material, attaching tannic acid to it. The introduction of tannic acid increases the material's ability to form a char layer during combustion, further improving its heat insulation and oxygen barrier effects, thereby enhancing its flame-retardant performance. The addition of ferric nitrate solution allows tannic acid to chelate iron ions. During combustion, these iron ions catalyze carbonization, accelerating the formation of a char layer on the material's surface. The char layer can prevent the transfer of heat and oxygen and reduce the generation of combustible gases, thereby significantly improving the flame retardant properties of the material.

[0019] Finally, tris(2,4-di-tert-butyl)phosphite, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanuric acid, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)triazine-2,4,6-(1H,3H,5H)trione, 2,4,6 One or more of the following, tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)trimethylbenzene and 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, are mixed evenly in a certain proportion to obtain a compound antioxidant; processing aid PPA, calcium stearate, β-nucleating agent powder, and color powder are mixed evenly, and then mixed evenly with the compound antioxidant to obtain an additive; polypropylene resin, additive, and auxiliaries are then mixed, and the mixture is melt-extruded, cooled, and drawn to obtain the finished product.

[0020] Tris(2,4-di-tert-butyl)phosphite, through its phosphite chemical structure, can decompose the hydroperoxides generated during polymer oxidation, reducing them to stable alcohols and blocking the chain reaction that leads to material degradation. This ensures processing stability and prevents thermo-oxidative degradation of the polymer during high-temperature processing (such as granulation and injection molding). Pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate can provide hydrogen atoms through phenolic hydroxyl groups, capturing free radicals and interrupting the chain reaction of oxidation. This provides long-term thermal stability, preventing oxidative degradation of the polymer during long-term use and high-temperature processing. Simultaneously, it can synergistically work with tris(2,4-di-tert-butyl)phosphite to address free radicals and hydroperoxides, significantly improving the processing stability and long-term thermal stability of PP. 1,3,5-Tris(3,5-di-tert-butyl-4-hydroxybenzyl)triazine-2,4,6-(1H,3H,5H)trione and tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanuric acid can capture free radicals through multiple hindered phenolic groups in the molecule, interrupting the chain reaction of oxidation, thereby providing long-term thermal stability and inhibiting the thermo-oxidative degradation of polymers during processing and use. At the same time, due to its special molecular structure, it has low reactivity with nitrogen oxides, which can effectively prevent yellowing of products caused by gas, automobile exhaust and other pollutants. Moreover, its high molecular weight makes it less prone to volatilization and migration during processing and use. The mechanism of action of 2,4,6-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)trimethylbenzyl is the same as that of tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanuric acid. Furthermore, 2,4,6-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)trimethylbenzyl exhibits excellent extractability, effectively preventing antioxidants from becoming ineffective due to water extraction. Its electrically neutral (zero dipole moment) characteristic ensures excellent insulation performance. 1,1,3-Tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane belongs to the polycyclic hindered phenolic antioxidant class. Its core function is as a highly efficient chain-terminating primary antioxidant, providing hydrogen atoms to capture free radicals and interrupt the oxidative degradation chain reaction of polypropylene (PP). Processing aid PPA benefits from the extremely low surface tension of fluoropolymers. During PP melt extrusion, it gradually migrates to the surface of the polymer melt, forming a continuous, dynamic lubricating film. This film significantly reduces friction between the polymer melt and the metal surface, eliminating surface defects caused by strong adhesion and shearing between the melt and the die. Calcium stearate, a weakly basic metal soap, effectively neutralizes acidic residues produced during PP polymerization. Furthermore, due to the poor compatibility of its polar head (calcium ions) with non-polar PP, it tends to migrate to the melt surface, forming a lubricating film that effectively reduces friction and adhesion.Meanwhile, the molecular structure of calcium stearate allows it to coat the surface of pigment or filler particles, improving their compatibility with the PP matrix. This helps these solid particles disperse more uniformly in the melt, preventing agglomeration and reducing color difference and performance inhomogeneity. β-nucleating agent powder acts as heterogeneous nucleation sites during the cooling and crystallization process of PP from the molten state, significantly lowering the energy barrier for β-crystal formation and preferentially inducing PP molecular chains to align into a β-crystal form on its surface. The blurred interfaces between the spherulites of β-crystals allow them to absorb a large amount of energy through crazing and shear bands upon impact, inducing a crystal transformation (β-crystal to α-crystal), thus consuming a significant amount of impact energy. Furthermore, β-crystal PP has a higher heat distortion temperature. Additionally, the greater number of connecting molecules between the lamellae of β-crystals helps improve the material's long-term creep resistance. Pigment powder selectively absorbs and scatters visible light through pigment particles, thus exhibiting specific colors and imparting color to the material. Attached Figure Description

[0021] Figure 1 (a) represents the density of Examples 1-6. Figure 1 (b) represents the melt mass flow rate in Examples 1-6. Figure 1 (c) represents the ash content of Examples 1-6. Figure 1 (d) represents the flexural modulus of Examples 1-6. Figure 1 (e) represents the tensile strength of Examples 1-6. Figure 1 (f) represents the impact strength of Examples 1-6. Figure 1 (g) represents the heat distortion temperature of Examples 1-6. Figure 1 (h) represents the Vicat softening temperature of Examples 1-6. Figure 1 (i) represents the oxidation induction temperature of Examples 1-6. Figure 1 (j) represents the molding shrinkage rate of Examples 1-6. Detailed Implementation

[0022] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0023] Raw material source: Multi-walled carbon nanotubes, with a diameter of 9.5 nm, were provided by Forsmann Technology (Beijing) Co., Ltd.; processing aid PPA was provided by Chenghe Technology Co., Ltd.; β-nucleating agent powder was provided by Chenghe Technology Co., Ltd.; color powder was provided by Shenzhen Huihong Plastic Auxiliary Materials Co., Ltd.; hydrotalcite, specifically magnesium aluminum hydrotalcite, was provided by Jingjiang Kanggaote New Material Technology Co., Ltd., with a fineness of 300 mesh; isopentenyl alcohol polyoxyethylene ether was provided by Hubei Langbowan Biomedical Co., Ltd., with a molecular weight of 2400.

[0024] Example 1: 0.3% tris(2,4-di-tert-butyl)phosphite, 0.25% pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 0.15% tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanuric acid, 0.3% 2,4,6-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)trimethylbenzylene, 0.05% processing aid PPA, 0.15% calcium stearate, 0.1% β-nucleating agent powder, and 0.2% colorant were mixed evenly to obtain an additive; then 98.5% polypropylene resin with a melt flow rate of 0.24 g / 10 min and 1.5% additive were mixed, and the mixture was melt-extruded, cooled, and drawn to obtain the finished product.

[0025] Example 2: 0.3% tris(2,4-di-tert-butyl)phosphite, 0.25% β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 0.15% tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanuric acid, 0.3% 2,4,6-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)trimethylbenzene, 0.1% processing aid PPA, 0.15% calcium stearate, 0.15% β-nucleating agent powder, and 0.2% colorant were mixed evenly to obtain an additive; then 98.4% polypropylene resin with a melt flow rate of 0.24 g / 10 min and 1.6% additive were mixed, and the mixture was melt-extruded, cooled, and drawn to obtain the finished product.

[0026] Example 3: 0.3% tris(2,4-di-tert-butyl)phosphite, 0.25% pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 0.15% 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)triazine-2,4,6-(1H,3H,5H)trione, 0.3% 2,4,6-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)trimethylbenzyl, 0.05% processing aid PPA, 0.15% calcium stearate, 0.1% β-nucleating agent powder, and 0.2% colorant were mixed evenly to obtain an additive; then 98.5% polypropylene resin with a melt flow rate of 0.28 g / 10 min and 1.5% additive were mixed, and the mixture was melt-extruded, cooled, and drawn to obtain the finished product.

[0027] Example 4: 0.3% tris(2,4-di-tert-butyl)phosphite, 0.25% pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 0.15% tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanuric acid, 0.15% 2,4,6-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)trimethylbenzene, 0.15% 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 0.1% processing aid PPA, 0.15% calcium stearate, 0.15% β-nucleating agent powder, and 0.2% colorant were mixed evenly to obtain an additive; then 98.4% polypropylene resin with a melt flow rate of 0.28 g / 10 min and 1.6% additive were mixed, and the mixture was melt-extruded, cooled, and drawn to obtain the finished product.

[0028] Example 5: 0.4% tris(2,4-di-tert-butyl)phosphite, 0.3% pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 0.25% 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)triazine-2,4,6-(1H,3H,5H)trione, 0.35% 2,4,6-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)trimethylbenzyl, 0.1% processing aid PPA, 0.2% calcium stearate, 0.2% β-nucleating agent powder, and 0.2% colorant were mixed evenly to obtain an additive; then 98% polypropylene resin with a melt flow rate of 0.28 g / 10 min and 2% additive were mixed, and the mixture was melt-extruded, cooled, and drawn to obtain the finished product.

[0029] Example 6: 0.5% tris(2,4-di-tert-butyl)phosphite, 0.3% β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 0.3% tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanuric acid, 0.5% 2,4,6-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)trimethylbenzene, 0.1% processing aid PPA, 0.3% calcium stearate, 0.2% β-nucleating agent powder, and 0.2% colorant were mixed evenly to obtain an additive; then 97.6% polypropylene resin with a melt flow rate of 0.28 g / 10 min and 2.4% additive were mixed, and the mixture was melt-extruded, cooled, and drawn to obtain the finished product.

[0030] Example 7: Step S1: Multi-walled carbon nanotubes were added to an acid solution and stirred at 95°C for 40 min. After the reaction, the mixture was cooled, diluted, filtered, washed with water, dried, and ground to obtain modified carbon nanotubes. The modified carbon nanotubes were added to a mixed solution and stirred at 30°C for 3 h. After the reaction, the mixture was washed, dried, and ground to obtain pretreated carbon nanotubes. The acid solution contained 8.4 mol / L concentrated nitric acid and 17 mol / L concentrated sulfuric acid in a volume ratio of 1:1. The mixed solution contained 0.13 g / L stannous chloride and 1.0 mol / L hydrochloric acid. Step S2: Add the pretreated carbon nanotubes to a 4 wt% silver ammonia solution and stir at 30°C for 30 min. Then add a 5.5 wt% glucose solution and continue stirring for 3.7 h. After stirring, filter, wash with water, dry, and grind to obtain CNTs-Ag. The mass-volume ratio of pretreated carbon nanotubes, silver ammonia solution, and glucose solution is 2 g: 50 mL: 45 mL. Step S3: Add CNTs-Ag to ethanol, disperse evenly by ultrasonication, then add 2-propen-1-thiol. Stir and react at 30°C for 8 hours under a nitrogen atmosphere. After the reaction is complete, wash with alcohol, filter, and dry to obtain propylene-based antistatic material; the mass-to-volume ratio of CNTs-Ag to 2-propen-1-thiol is 2g:0.45mL. Step S4: Under a nitrogen atmosphere, isopentenyl alcohol polyoxyethylene ether, maleic anhydride, and propylene-based antistatic material are added to deionized water and stirred until homogeneous. Hydrogen peroxide is then added, followed by dropwise addition of ferrous chloride aqueous solution. After the addition is complete, the mixture is reacted at 40°C for 7 hours. After the reaction is complete, the mixture is cooled, washed, distilled under reduced pressure, precipitated, filtered, washed again, and dried to obtain the antistatic material. The mass ratio of isopentenyl alcohol polyoxyethylene ether, maleic anhydride, and propylene-based antistatic material is 3:1:0.6. Step S5: Under a nitrogen atmosphere, add hydrotalcite to the mixed solution and stir at 55°C for 40 min. After stirring, slowly add the silane coupling agent solution, adjust the pH of the solution to 4, and reflux at 90°C for 30 h. After the reaction, cool, filter, wash, and dry to obtain the modified hydrotalcite material. The mixed solution includes ethanol and deionized water in a volume ratio of 1.1:3. The silane coupling agent solution includes γ-aminopropyltriethoxysilane, ethanol, and deionized water in a mass-to-volume ratio of 0.11 g: 10 mL: 1 mL. The mass ratio of hydrotalcite to γ-aminopropyltriethoxysilane is 1:0.09. Step S6: Add hexachlorocyclotriphosphazene and the acid-binding agent ethylenediaminetetraacetic acid to tetrahydrofuran, and disperse evenly by ultrasonication to obtain a reaction solution; add the modified hydrotalcite material to tetrahydrofuran, disperse evenly by ultrasonication, and then add the reaction solution. Stir and react at 65℃ for 12 hours. After the reaction is completed, cool, filter, wash, and dry to obtain the flame-retardant hydrotalcite material; the reaction mass ratio of hexachlorocyclotriphosphazene, ethylenediaminetetraacetic acid, and modified hydrotalcite material is 1:0.63:19. Step S7: Add tannic acid to acetonitrile, stir evenly at 60°C, then add flame-retardant hydrotalcite material, continue stirring and heating for 40 minutes, then raise the temperature to 80°C, and add anhydrous magnesium chloride at the same time, continue stirring and reacting for 3.0 hours, then add acid-binding agent pyridine, and continue reacting for 3 hours. After the reaction is completed, filter, wash and dry to obtain flame-retardant material; the mass ratio of tannic acid to flame-retardant hydrotalcite material is 1:16. Step S8: Add the flame retardant material to deionized water, disperse it evenly, and then add 16.5 g / L of ferric nitrate solution dropwise. After the addition is complete, react at 30°C for 3.5 h. After the reaction is complete, filter, wash, dry, and grind to obtain the composite flame retardant material. Step S9: Mix 0.2% tris(2,4-di-tert-butyl)phosphite, 0.2% pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 0.2% tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanuric acid, 0.2% 2,4,6-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)trimethylbenzene, 0.05% processing aid PPA, 0.2% calcium stearate, 0.2% β-nucleating agent powder, and 0.3% color powder evenly to obtain the additive; then mix 79.45% polypropylene resin with a melt flow rate of 0.24 g / 10 min, 2.0% antistatic material, 17% composite flame retardant material, and 1.55% additive, and melt extrude, cool, and pull to obtain the finished product; the melt extrusion temperature is 210℃.

[0031] Example 8: Step S1: Multi-walled carbon nanotubes were added to an acid solution and stirred at 90°C for 35 min. After the reaction, the mixture was cooled, diluted, filtered, washed with water, dried, and ground to obtain modified carbon nanotubes. The modified carbon nanotubes were added to a mixed solution and stirred at 27°C for 2.5 h. After the reaction, the mixture was washed, dried, and ground to obtain pretreated carbon nanotubes. The acid solution contained 8.4 mol / L concentrated nitric acid and 17 mol / L concentrated sulfuric acid in a volume ratio of 1:1. The mixed solution contained 0.13 g / L stannous chloride and 1.0 mol / L hydrochloric acid. Step S2: Add the pretreated carbon nanotubes to a 4 wt% silver ammonia solution and stir at 27°C for 25 min. Then add a 5.5 wt% glucose solution and continue stirring for 3.7 h. After stirring, filter, wash with water, dry, and grind to obtain CNTs-Ag. The mass-volume ratio of pretreated carbon nanotubes, silver ammonia solution, and glucose solution is 2 g: 50 mL: 45 mL. Step S3: Add CNTs-Ag to ethanol, disperse evenly by ultrasonication, then add 2-propen-1-thiol. Stir and react at 27°C for 7.5 h under a nitrogen atmosphere. After the reaction is complete, wash with alcohol, filter, and dry to obtain propylene-based antistatic material; the mass-to-volume ratio of CNTs-Ag to 2-propen-1-thiol is 2 g: 0.45 mL. Step S4: Under a nitrogen atmosphere, isopentenyl alcohol polyoxyethylene ether, maleic anhydride, and propylene-based antistatic material were added to deionized water and stirred until homogeneous. Hydrogen peroxide was then added, followed by dropwise addition of ferrous chloride aqueous solution. After the addition was complete, the mixture was reacted at 37°C for 6 hours. After the reaction was completed, the mixture was cooled, washed, distilled under reduced pressure, precipitated, filtered, washed, and dried to obtain the antistatic material. The mass ratio of isopentenyl alcohol polyoxyethylene ether, maleic anhydride, and propylene-based antistatic material was 3:1:0.6. Step S5: Under a nitrogen atmosphere, add hydrotalcite to the mixed solution and stir at 53°C for 35 min. After stirring, slowly add the silane coupling agent solution, adjust the pH of the solution to 3-4, and reflux at 85°C for 27 h. After the reaction, cool, filter, wash, and dry to obtain the modified hydrotalcite material. The mixed solution includes ethanol and deionized water in a volume ratio of 1.1:3. The silane coupling agent solution includes γ-aminopropyltriethoxysilane, ethanol, and deionized water in a mass-to-volume ratio of 0.11 g: 10 mL: 1 mL. The mass ratio of hydrotalcite to γ-aminopropyltriethoxysilane is 1:0.09. Step S6: Add hexachlorocyclotriphosphazene and the acid-binding agent ethylenediaminetetraacetic acid to tetrahydrofuran, and disperse evenly by ultrasonication to obtain a reaction solution; add the modified hydrotalcite material to tetrahydrofuran, disperse evenly by ultrasonication, and then add the reaction solution. Stir and react at 62℃ for 10 hours. After the reaction is completed, cool, filter, wash, and dry to obtain the flame-retardant hydrotalcite material; the reaction mass ratio of hexachlorocyclotriphosphazene, ethylenediaminetetraacetic acid, and modified hydrotalcite material is 1:0.63:19. Step S7: Add tannic acid to acetonitrile, stir evenly at 57°C, then add flame-retardant hydrotalcite material, continue stirring and heating for 30-40 minutes, then raise the temperature to 78°C, and simultaneously add anhydrous magnesium chloride. Continue stirring and reacting for 2.7 hours, then add the acid-binding agent pyridine, and continue reacting for 2 hours. After the reaction is complete, filter, wash, and dry to obtain the flame-retardant material; the mass ratio of tannic acid to flame-retardant hydrotalcite material is 1:16. Step S8: Add the flame retardant material to deionized water, disperse it evenly, and then add 16.5 g / L of ferric nitrate solution dropwise. After the addition is complete, react at 27°C for 3.2 h. After the reaction is complete, filter, wash, dry, and grind to obtain the composite flame retardant material. Step S9: Mix 0.2% tris(2,4-di-tert-butyl)phosphite, 0.2% pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 0.2% tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanuric acid, 0.2% 2,4,6-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)trimethylbenzene, 0.05% processing aid PPA, 0.2% calcium stearate, 0.2% β-nucleating agent powder, and 0.3% color powder evenly to obtain the additive; then mix 79.45% polypropylene resin, 2.0% antistatic material, 17% composite flame retardant material, and 1.55% additive with a melt flow rate of 0.24 g / 10 min, and obtain the finished product through melt extrusion, cooling, and traction; the melt extrusion temperature is 195℃.

[0032] Example 9: Step S1: Multi-walled carbon nanotubes were added to an acid solution and stirred at 85°C for 30 min. After the reaction, the mixture was cooled, diluted, filtered, washed with water, dried, and ground to obtain modified carbon nanotubes. The modified carbon nanotubes were added to a mixed solution and stirred at 25°C for 2 h. After the reaction, the mixture was washed, dried, and ground to obtain pretreated carbon nanotubes. The acid solution contained 8.4 mol / L concentrated nitric acid and 17 mol / L concentrated sulfuric acid in a volume ratio of 1:1. The mixed solution contained 0.13 g / L stannous chloride and 1.0 mol / L hydrochloric acid. Step S2: Add the pretreated carbon nanotubes to a 4 wt% silver ammonia solution and stir at 25°C for 20 min. Then add a 5.5 wt% glucose solution and continue stirring for 3.7 h. After stirring, filter, wash with water, dry, and grind to obtain CNTs-Ag. The mass-volume ratio of pretreated carbon nanotubes, silver ammonia solution, and glucose solution is 2 g: 50 mL: 45 mL. Step S3: Add CNTs-Ag to ethanol, disperse evenly by ultrasonication, then add 2-propen-1-thiol. Stir and react at 25°C for 7-8 hours under a nitrogen atmosphere. After the reaction is complete, wash with alcohol, filter, and dry to obtain propylene-based antistatic material; the mass-to-volume ratio of CNTs-Ag to 2-propen-1-thiol is 2g:0.45mL. Step S4: Under a nitrogen atmosphere, isopentenyl alcohol polyoxyethylene ether, maleic anhydride, and propylene-based antistatic material are added to deionized water and stirred until homogeneous. Hydrogen peroxide is then added, followed by dropwise addition of ferrous chloride aqueous solution. After the addition is complete, the mixture is reacted at 35°C for 5 hours. After the reaction is complete, the mixture is cooled, washed, distilled under reduced pressure, precipitated, filtered, washed, and dried to obtain the antistatic material. The mass ratio of isopentenyl alcohol polyoxyethylene ether, maleic anhydride, and propylene-based antistatic material is 3:1:0.6. Step S5: Under a nitrogen atmosphere, add hydrotalcite to the mixed solution and stir at 50°C for 30 min. After stirring, slowly add the silane coupling agent solution, adjust the pH of the solution to 3, and reflux at 80°C for 25 h. After the reaction, cool, filter, wash, and dry to obtain the modified hydrotalcite material. The mixed solution includes ethanol and deionized water in a volume ratio of 1.1:3. The silane coupling agent solution includes γ-aminopropyltriethoxysilane, ethanol, and deionized water in a mass-to-volume ratio of 0.11 g: 10 mL: 1 mL. The mass ratio of hydrotalcite to γ-aminopropyltriethoxysilane is 1:0.09. Step S6: Add hexachlorocyclotriphosphazene and the acid-binding agent ethylenediaminetetraacetic acid to tetrahydrofuran, and disperse evenly by ultrasonication to obtain a reaction solution; add the modified hydrotalcite material to tetrahydrofuran, disperse evenly by ultrasonication, and then add the reaction solution. Stir and react at 60℃ for 9 hours. After the reaction is completed, cool, filter, wash, and dry to obtain the flame-retardant hydrotalcite material; the reaction mass ratio of hexachlorocyclotriphosphazene, ethylenediaminetetraacetic acid, and modified hydrotalcite material is 1:0.63:19. Step S7: Add tannic acid to acetonitrile, stir evenly at 55°C, then add flame-retardant hydrotalcite material, continue stirring and heating for 30 minutes, then raise the temperature to 75°C, and add anhydrous magnesium chloride. Continue stirring and reacting for 2.5 hours, then add acid-binding agent pyridine, and continue reacting for 1 hour. After the reaction is completed, filter, wash, and dry to obtain the flame-retardant material; the mass ratio of tannic acid to flame-retardant hydrotalcite material is 1:16. Step S8: Add the flame retardant material to deionized water, disperse it evenly, and then add 16.5 g / L of ferric nitrate solution dropwise. After the addition is complete, react at 25°C for 3.0 h. After the reaction is complete, filter, wash, dry, and grind to obtain the composite flame retardant material. Step S9: Mix 0.2% tris(2,4-di-tert-butyl)phosphite, 0.2% pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 0.2% tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanuric acid, 0.2% 2,4,6-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)trimethylbenzene, 0.05% processing aid PPA, 0.2% calcium stearate, 0.2% β-nucleating agent powder, and 0.3% color powder evenly to obtain the additive; then mix 79.45% polypropylene resin with a melt flow rate of 0.24 g / 10 min, 2.0% antistatic material, 17% composite flame retardant material, and 1.55% additive, and melt extrude, cool, and pull to obtain the finished product; the melt extrusion temperature is 180℃.

[0033] Comparative Example 1: The antistatic material was removed, and the rest was the same as in Example 7. The specific steps are as follows: Step S1: Under a nitrogen atmosphere, hydrotalcite was added to the mixed solution and stirred at 55°C for 40 min. After stirring, the silane coupling agent solution was slowly added, and the pH of the solution was adjusted to 4. The solution was refluxed at 90°C for 30 h. After the reaction, the solution was cooled, filtered, washed, and dried to obtain the modified hydrotalcite material. The mixed solution included ethanol and deionized water in a volume ratio of 1.1:3. The silane coupling agent solution included γ-aminopropyltriethoxysilane, ethanol, and deionized water in a mass-volume ratio of 0.11 g: 10 mL: 1 mL. The mass ratio of hydrotalcite to γ-aminopropyltriethoxysilane was 1:0.09. Step S2: Hexachlorocyclotriphosphazene and the acid-binding agent ethylenediaminetetraacetic acid were added to tetrahydrofuran and ultrasonically dispersed to obtain a reaction solution; the modified hydrotalcite material was added to tetrahydrofuran and ultrasonically dispersed to obtain a reaction solution, and the mixture was stirred at 65°C for 12 hours. After the reaction was completed, the mixture was cooled, filtered, washed, and dried to obtain the flame-retardant hydrotalcite material; the mass ratio of hexachlorocyclotriphosphazene, ethylenediaminetetraacetic acid, and modified hydrotalcite material was 1:0.63:19. Step S3: Add tannic acid to acetonitrile, stir evenly at 60°C, then add flame-retardant hydrotalcite material, continue stirring and heating for 40 minutes, then raise the temperature to 80°C, and add anhydrous magnesium chloride at the same time, continue stirring and reacting for 3.0 hours, then add acid-binding agent pyridine, and continue reacting for 3 hours. After the reaction is completed, filter, wash and dry to obtain flame-retardant material; the mass ratio of tannic acid to flame-retardant hydrotalcite material is 1:16. Step S4: Add the flame retardant material to deionized water, disperse it evenly, and then add 16.5 g / L of ferric nitrate solution dropwise. After the addition is complete, react at 30°C for 3.5 h. After the reaction is complete, filter, wash, dry, and grind to obtain the composite flame retardant material. Step S5: Mix 0.2% tris(2,4-di-tert-butyl)phosphite, 0.2% pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 0.2% tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanuric acid, 0.2% 2,4,6-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)trimethylbenzylene, 0.05% processing aid PPA, 0.2% calcium stearate, 0.2% β-nucleating agent powder, and 0.3% colorant evenly to obtain the additive; then mix 81.45% polypropylene resin with a melt flow rate of 0.24 g / 10 min, 17% composite flame retardant material, and 1.55% additive, and melt extrude, cool, and pull to obtain the finished product; the melt extrusion temperature is 210℃.

[0034] Comparative Example 2: The composite flame retardant material was removed, and the rest was the same as in Example 7. The specific steps are as follows: Step S1: Multi-walled carbon nanotubes were added to the acid solution and stirred at 95°C for 40 min. After the reaction, the mixture was cooled, diluted, filtered, washed with water, dried, and ground to obtain modified carbon nanotubes. The modified carbon nanotubes were added to the mixed solution and stirred at 30°C for 3 h. After the reaction, the mixture was washed, dried, and ground to obtain pretreated carbon nanotubes. The acid solution contained 8.4 mol / L concentrated nitric acid and 17 mol / L concentrated sulfuric acid in a volume ratio of 1:1. The mixed solution contained 0.13 g / L stannous chloride and 1.0 mol / L hydrochloric acid. Step S2: Add the pretreated carbon nanotubes to a 4 wt% silver ammonia solution and stir at 30°C for 30 min. Then add a 5.5 wt% glucose solution and continue stirring for 3.7 h. After stirring, filter, wash with water, dry, and grind to obtain CNTs-Ag. The mass-volume ratio of pretreated carbon nanotubes, silver ammonia solution, and glucose solution is 2 g: 50 mL: 45 mL. Step S3: Add CNTs-Ag to ethanol, disperse evenly by ultrasonication, then add 2-propen-1-thiol. Stir and react at 30°C for 8 hours under a nitrogen atmosphere. After the reaction is complete, wash with alcohol, filter, and dry to obtain propylene-based antistatic material; the mass-to-volume ratio of CNTs-Ag to 2-propen-1-thiol is 2g:0.45mL. Step S4: Under a nitrogen atmosphere, isopentenyl alcohol polyoxyethylene ether, maleic anhydride, and propylene-based antistatic material are added to deionized water and stirred until homogeneous. Hydrogen peroxide is then added, followed by dropwise addition of ferrous chloride aqueous solution. After the addition is complete, the mixture is reacted at 40°C for 7 hours. After the reaction is complete, the mixture is cooled, washed, distilled under reduced pressure, precipitated, filtered, washed again, and dried to obtain the antistatic material. The mass ratio of isopentenyl alcohol polyoxyethylene ether, maleic anhydride, and propylene-based antistatic material is 3:1:0.6. Step S5: Mix 0.2% tris(2,4-di-tert-butyl)phosphite, 0.2% pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 0.2% tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanuric acid, 0.2% 2,4,6-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)trimethylbenzene, 0.05% processing aid PPA, 0.2% calcium stearate, 0.2% β-nucleating agent powder, and 0.3% color powder evenly to obtain the additive; then mix 96.45% polypropylene resin with a melt flow rate of 0.24 g / 10 min, 2.0% antistatic material, and 1.55% additive, and melt extrude, cool, and pull to obtain the finished product; the melt extrusion temperature is 210℃.

[0035] Testing and experimentation: Density determination: The density of the high-performance polypropylene resins for chemical pipes prepared in Examples 1-6 was measured according to GB / T 17037.1-2019, and the density was recorded. The results are shown in Table 1 below.

[0036] Melt flow rate determination: Referring to GB / T 3682.1-2018, the melt flow rate of the high-performance chemical pipe polypropylene resin prepared in Examples 1-6 was measured using a melt flow rate meter, and the melt flow rate was read. The results are shown in Table 1 below.

[0037] Ash content determination: The ash content of the high-performance chemical pipes prepared in Examples 1-6 was measured according to GB / T 9345.1-2008, and the ash content was recorded. The results are shown in Table 1 below.

[0038] Flexural modulus determination: The flexural modulus of the high-performance chemical pipes prepared in Examples 1-6 was measured according to GB / T 9341-2008, and the flexural modulus was read. The results are shown in Table 1 below.

[0039] Tensile strength test: The tensile strength of the high-performance chemical pipes prepared in Examples 1-6 was measured according to GB / T 1040.2-2022, and the tensile strength was recorded. The results are shown in Table 1 below.

[0040] Impact strength test: The polypropylene resins for high-performance chemical pipes prepared in Examples 1-6 were subjected to simple-supported beam impact tests according to GB / T 1043.1-2008, and the impact strength was read. The results are shown in Table 1 below.

[0041] Heat distortion temperature determination: The heat distortion temperature of the high-performance chemical pipes prepared in Examples 1-6 was measured according to GB / T 1634.2-2019, and the heat distortion temperature was read. The results are shown in Table 1 below.

[0042] Vicat softening temperature determination: The Vicat softening temperature of the high-performance chemical pipe polypropylene resins prepared in Examples 1-6 was measured according to GB / T 1633-2000, and the Vicat softening temperature was recorded. The results are shown in Table 1 below.

[0043] Oxidation induction temperature determination: The oxidation induction temperature of the high-performance chemical pipes prepared in Examples 1-6 was measured according to GB / T 19466.6-2009, and the oxidation induction temperature was recorded. The results are shown in Table 1 below.

[0044] Molding shrinkage rate determination: The shrinkage rate of the high-performance chemical pipes prepared in Examples 1-6 was measured in both vertical and horizontal directions according to GB / T 17037.4-2003. The results are shown in Table 1 below.

[0045] Flame retardant performance test: Referring to GB / T 2406.2-2009, the high-performance polypropylene chemical pipe prepared by this invention was cut into samples with dimensions of 120×10×4mm, and the oxygen index value was tested and recorded. The results are shown in Table 2 below.

[0046] Antistatic performance test: Referring to GB / T 31838.3-2019, the high-performance polypropylene chemical pipe prepared by this invention was cut into 60mm×60mm samples, and the antistatic performance of the samples was tested. The results are shown in Table 2 below.

[0047] Table 1 Table 2 Conclusion: Based on the above data and Examples 1-6, we can conclude that this invention utilizes a β-nucleating agent as a heterogeneous nucleation site, significantly reducing the energy barrier of the β-crystal form and inducing its formation, thus producing high-performance polypropylene chemical pipes. The polypropylene resin obtained by this invention exhibits uniform density, stable melt flow rate, low ash content, excellent mechanical properties, stable heat distortion temperature, Vicat softening temperature, and oxidation induction temperature, and low molding shrinkage, demonstrating superior performance. Compared with similar domestic products, the polypropylene resin obtained by this invention has lower ash content, higher flexural modulus, essentially consistent tensile strength, significantly improved simply supported beam impact strength, essentially consistent heat distortion temperature and Vicat softening temperature, significantly improved oxidation induction time, and significantly reduced molding shrinkage. Compared with similar foreign products, the polypropylene resin obtained by this invention has significantly lower ash content, significantly improved flexural modulus and tensile strength, essentially consistent simply supported beam impact strength, improved heat distortion temperature and Vicat softening temperature, significantly improved oxidation induction time, and significantly reduced molding shrinkage.

[0048] Examples 7-9 used the same dosages, only modifying some reaction parameters. Experimental data showed no significant fluctuations in the properties of the samples. Comparative Example 1: The antistatic material was removed, and everything else was the same as in Example 1. Experimental data showed that, compared to Example 1, the surface resistivity increased to 3.8 × 10⁻⁶. 13 The reason for the Ω / sq is that the antistatic material prepared by this invention contains multiple conductive antistatic structures such as carbon nanotubes and silver particles. Therefore, without the use of antistatic materials, the surface resistivity increases and the antistatic properties decrease.

[0049] Comparative Example 2: The composite flame retardant material was removed, and the rest was the same as in Example 1. The experimental data showed that the flame retardant oxygen index was reduced to 18.7% compared with Example 1. The reason for this is that the composite flame retardant material includes synergistic flame retardant structures such as hydrotalcite, nitrogen, and phosphorus, and therefore has excellent flame retardant properties. So, without the composite flame retardant material, the oxygen index and flame retardancy are reduced.

[0050] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process method article or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process method article or apparatus.

[0051] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing high-performance polypropylene chemical pipes, characterized in that: Includes the following steps: One or more of the following ingredients are mixed in a specific ratio to prepare a compound antioxidant: tris(2,4-di-tert-butyl)phosphite, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanuric acid, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)triazine-2,4,6-(1H,3H,5H)trione, 2,4,6-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)trimethylbenzylene, and 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane. After the processing aid PPA, calcium stearate, β-nucleating agent powder and color powder are mixed evenly, they are then mixed evenly with the compound antioxidant to obtain the additive. The polypropylene resin, additives, and auxiliaries are then mixed, melt-extruded, cooled, and drawn to obtain the finished product.

2. The method for preparing a high-performance polypropylene chemical pipe according to claim 1, characterized in that: The content of each component in the finished product is as follows (by mass fraction): tris(2,4-di-tert-butyl)phosphite 0.1%-0.5%, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate octadecyl alcohol 0.1%-0.5%, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] 0.1%-0.5%, tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanuric acid 0.1%-0.5%, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)triazine-2,4,6-(1 H,3H,5H)trione 0.1%-0.5%, 2,4,6-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)trimethylbenzene 0.1%-0.5%, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane 0.1%-0.5%, processing aid PPA 0.01%-0.1%, calcium stearate 0.1%-0.5%, β-nucleating agent powder 0.1%-0.5%, colorant 0.1%-0.5%, 0-23% additives, balance polypropylene resin; melt extrusion temperature is 180-210℃.

3. The method for preparing a high-performance polypropylene chemical pipe according to claim 2, characterized in that: The additives are obtained by compounding antistatic materials and composite flame retardant materials in a mass ratio of (1.5-3.0):(15-20).

4. The method for preparing a high-performance polypropylene chemical pipe according to claim 3, characterized in that: The preparation process of antistatic materials is as follows: Step S1: Add multi-walled carbon nanotubes to the acid solution and stir at 85-95℃ for 30-40 min. After the reaction is completed, cool, dilute, filter, wash with water, dry and grind to obtain modified carbon nanotubes. Modified carbon nanotubes were added to the mixture and stirred at 25-30℃ for 2-3 hours. After the reaction was completed, the mixture was washed, dried and ground to obtain pretreated carbon nanotubes. Step S2: Add the pretreated carbon nanotubes to a 3-5 wt% silver ammonia solution and stir at 25-30℃ for 20-30 min. Then add a 5-6 wt% glucose solution and continue stirring for 3.5-4.0 h. After stirring, filter, wash with water, dry and grind to obtain CNTs-Ag. Step S3: Add CNTs-Ag to ethanol, disperse evenly by ultrasonication, then add 2-propen-1-thiol, and stir the reaction at 25-30℃ for 7-8 hours under a nitrogen atmosphere. After the reaction is completed, wash with alcohol, filter and dry to obtain propylene-based antistatic material. Step S4: Under a nitrogen atmosphere, add isopentenyl alcohol polyoxyethylene ether, maleic anhydride, and propylene antistatic material to deionized water, stir evenly, add hydrogen peroxide, and then add ferrous chloride aqueous solution dropwise. After the addition is complete, react at 35-40℃ for 5-7 hours. After the reaction is complete, cool, wash, distill under reduced pressure, precipitate, filter, wash, and dry to obtain the antistatic material.

5. The method for preparing a high-performance polypropylene chemical pipe according to claim 4, characterized in that: The acid solution contains 8.3-8.5 mol / L concentrated nitric acid and 16-18 mol / L concentrated sulfuric acid in a volume ratio of 1:1; the mixed solution contains 0.12-0.14 g / L stannous chloride and 1.0-1.1 mol / L hydrochloric acid; the mass-volume ratio of the pretreated carbon nanotubes, silver ammonia solution, and glucose solution is 2 g: 50 mL: (40-50) mL.

6. The method for preparing a high-performance polypropylene chemical pipe according to claim 4, characterized in that: The mass-volume ratio of CNTs-Ag and 2-propen-1-thiol is 2g:(0.4-0.5)mL; the reaction mass ratio of isopentenyl alcohol polyoxyethylene ether, maleic anhydride, and propylene antistatic material is 3:1:(0.5-0.7).

7. The method for preparing a high-performance polypropylene chemical pipe according to claim 3, characterized in that: The preparation process of composite flame retardant materials is as follows: Step S1: Under a nitrogen atmosphere, add hydrotalcite to the mixed solution and stir at 50-55℃ for 30-40 min. After stirring, slowly add silane coupling agent solution, adjust the pH of the solution to 3-4, and reflux at 80-90℃ for 25-30 h. After the reaction is completed, cool, filter, wash and dry to obtain modified hydrotalcite material. Step S2: Add hexachlorocyclotriphosphazene and the acid-binding agent ethylenediaminetetraacetic acid to tetrahydrofuran, and disperse evenly by ultrasonication to obtain a reaction solution; add the modified hydrotalcite material to tetrahydrofuran, disperse evenly by ultrasonication, and then add the reaction solution. Stir and react at 60-65℃ for 9-12 hours. After the reaction is completed, cool, filter, wash and dry to obtain the flame-retardant hydrotalcite material. Step S3: Add tannic acid to acetonitrile, stir evenly at 55-60℃, then add flame-retardant hydrotalcite material, continue stirring and heating for 30-40 minutes, then raise the temperature to 75-80℃, and add anhydrous magnesium chloride at the same time, continue stirring and reacting for 2.5-3.0 hours, then add acid-binding agent pyridine, and continue reacting for 1-3 hours. After the reaction is completed, filter, wash and dry to obtain flame-retardant material; Step S4: Add the flame retardant material to deionized water, disperse it evenly, and then add 16-17 g / L of ferric nitrate solution dropwise. After the addition is complete, react at 25-30℃ for 3.0-3.5 h. After the reaction is complete, filter, wash, dry, and grind to obtain the composite flame retardant material.

8. The method for preparing a high-performance polypropylene chemical pipe according to claim 7, characterized in that: In step S1, the mixed solution includes ethanol and deionized water in a volume ratio of (1.0-1.2):3; the silane coupling agent solution includes γ-aminopropyltriethoxysilane, ethanol, and deionized water in a mass-volume ratio of (0.10-0.12) g:10 mL:1 mL; when preparing the modified hydrotalcite material, the reaction mass ratio of hydrotalcite and γ-aminopropyltriethoxysilane is 1:(0.08-0.10).

9. The method for preparing a high-performance polypropylene chemical pipe according to claim 7, characterized in that: The reaction mass ratio of hexachlorocyclotriphosphazene, ethylenediaminetetraacetic acid, and modified hydrotalcite material is 1:0.63:(18-20); the reaction mass ratio of tannic acid and flame-retardant hydrotalcite material is 1:(15-17).

10. A high-performance polypropylene chemical pipe, characterized in that, Prepared by the preparation method according to any one of claims 1-9.